2020
DOI: 10.1039/d0cp04397d
|View full text |Cite
|
Sign up to set email alerts
|

A novel amalgamation of deep eutectic solvents and crowders as biocompatible solvent media for enhanced structural and thermal stability of bovine serum albumin

Abstract: Proteins have immense untapped potential in numerous industries as a green catalyst. Thus, there is an emergent need to find a suitable co-solvent that is biocompatible with protein and environmentally...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 48 publications
1
35
0
Order By: Relevance
“…3. This enhancement in the size of the BSA structure at a high concentration of reline has already been perceived experimentally by Bhakuni et al 26 Both the RMSD plot as well as the equilibrium snapshots demonstrate that the BSA conformation in pure reline is quite close to the native conformation.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…3. This enhancement in the size of the BSA structure at a high concentration of reline has already been perceived experimentally by Bhakuni et al 26 Both the RMSD plot as well as the equilibrium snapshots demonstrate that the BSA conformation in pure reline is quite close to the native conformation.…”
Section: Resultssupporting
confidence: 74%
“…The study concludes that for any DES to serve as a crystallization medium, the interactions within DES components should be stronger than the DES–protein interactions. Moreover, Bhakuni et al 26 recognized the remarkable thermal stability elevating effect of reline on the bovine serum albumin (BSA) protein in pure DES as well as in the presence of various crowders. Despite the presence of high amount of urea, a conventional protein denaturant, these assessments disclose the interesting role of reline in modulating protein thermal and conformational stability.…”
Section: Introductionmentioning
confidence: 99%
“…A majority of the papers reviewed in this section utilize either E. coli , [ 157 , 160 , 161 , 170 , 190 ] Staphylococcus aureus , [ 184 , 192 ] or both [ 153 , 154 , 155 , 156 , 158 , 162 , 165 , 166 , 168 , 169 , 171 , 173 , 174 , 176 , 183 , 184 ] to test IL/formulation bactericidal efficacy. The two bacterial strains are extremely clinically relevant, as these are both common bacterial infections in humans, and they E. coli and S. aureus represent two general categories of bacteria, Gram‐negative and Gram‐positive, respectively.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…BSA thermal stability has subsequently been improved by 16 °C using polyethylene glycol and choline chloride urea. [160] And 𝛽-lactoglobulin experiences structural changes when exposed to choline iodide, but those effects can be negated by the addition of choline dihydrogen phosphate. [161] ILs have also shown great promise in enzyme activity retention.…”
Section: -Methylimidazolium Hexafluorophosphate-based Ils ([Bmim][scn...mentioning
confidence: 99%
“…Dai group (Dai, Rozema, Verpoorte, & Choi, 2016) found that among the employed, cyanidins exhibited an at least three times higher stabilizing capacity in natural deep eutectic solvent (NADES) than in ethanol, which facilitated their extraction and analysis process. In addition, the mixture of DESs and crowders enhanced structural and thermal stability of bovine serum albuminas (Bhakuni, Yadav, & Venkatesu, 2020). A NADES composed by betaine and urea increased the stability of β‐lactam antibiotic clavulanic acid and imipenem by 7 and 2.5 fold compared to water, respectively, when 7 days after being dissolved (Olivares et al, 2018).…”
Section: Introductionmentioning
confidence: 99%